Visible Light‐Induced Regioselective Decarboxylative Alkylation of the C(sp2)−H Bonds of Non‐Aromatic Heterocycles. Issue 17 (19th July 2019) - Liu, Lixin; Pan, Neng; Sheng, Wei; Su, Lebin; Liu, Long; Dong, Jianyu; Zhou, Yongbo; Yin, Shuang‐Feng
Abstract: With sunlight or blue LEDs irradiation, regioselective decarboxylative alkylation of various non‐aromatic heterocycles has been realized via C( sp 3 )‐centered radical C( sp 2 )−C( sp 3 ) bond formation under oxidant‐free conditions at room temperature. This reaction readily incorporates various functional alkyl groups into heterocyclic compounds without observation of any alkyl radical rearrangement and represents a mild and general tool for the preparation of valuable alkyl group‐functionalized heterocyclic compounds. Abstract :